Persistent Antiphospholipid Antibodies Are Not Associated With Worse Clinical Outcomes in a Prospective Cohort of Hospitalised Patients With SARS-CoV-2 Infection - Espinosa, Gerard; Zamora-Martínez, Carles; Pérez-Isidro, Albert; Neto, Daniela; Bravo-Gallego, Luz Yadira; Prieto-González, Sergio; Viñas, Odette; Moreno-Castaño, Ana Belen; Ruiz-Ortiz, Estíbaliz; Cervera, Ricard; , The COVAPS-CLINIC Study Group Investigators; Almuedo, Alex; et al. (Frontiers in Immunology, 2022)
Objective: Patients with COVID-19 presented with an elevated prevalence of antiphospholipid antibodies (aPL) but the relationship with thrombosis is controversial. We analysed the persistence of aPL and their association with the clinical outcomes during hospitalisation in a cohort of COVID-19 patients. Patients and methods: We conducted a prospective study including consecutive hospitalised patients with COVID-19 from Hospital Clínic of Barcelona between March 28th and April 22nd, 2020. Clinical outcomes during hospitalisation were thrombosis, intensive care unit (ICU) admission, and severe ventilatory failure. We determined both criteria and non-criteria aPL. Of note, in those patients with a positive result in the first determination, a second sample separated by at least 12 weeks was drawn to test the persistence of aPL. Results: One hundred and fifty-eight patients (59.5% men) with a mean age of 61.4 ± 14.9 years old were included. Thrombosis was present in 28 (17.7%) patients, severe respiratory failure in 47 (30.5%), and 30 (18.9%) patients were admitted to ICU. Sixteen (28.6%) patients were positive for the criteria aPL at both determinations and only two (3.6%) of them suffered from thrombosis during hospitalisations (both had aCL IgG). However, they presented with low titers of aCL. Of note, aPL were not related to thrombosis, ICU admission or severe respiratory failure. Conclusion: Although aPL were prevalent in our cohort of hospitalised COVID-19 patients and they were persistent in half of tested patients, most determinations were at low titers and they were not related to worse clinical outcomes.